2011
DOI: 10.1097/aln.0b013e318223ba6d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Head Elevation on Passive Upper Airway Collapsibility in Normal Subjects during Propofol Anesthesia

Abstract: Background Head elevation can restore airway patency during anesthesia, although its effect may be offset by concomitant bite opening or accidental neck flexion. The aim of this study is to examine the effect of head elevation on the passive upper airway collapsibility during propofol anesthesia. Method Twenty male subjects were studied, randomized to one of two experimental groups: Fixed-jaw or Free-jaw. Propofol infusion was used for induction and to maintain blood concentration constant at a target level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 44 publications
0
24
0
1
Order By: Relevance
“…Arousals can therefore interfere with the assessment of compensatory upper‐airway and respiratory timing responses. We have previously reported that passive measurements of upper‐airway collapsibility in sedated subjects were similar to those in non‐REM sleep (Ayuse et al., 2004; Hoshino et al., 2009; Inazawa et al., 2005; Kobayashi et al., 2011). Active compensatory neuromuscular responses to partial upper‐airway obstruction have also been characterized in anesthetized subjects (Hoshino et al., 2009).…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…Arousals can therefore interfere with the assessment of compensatory upper‐airway and respiratory timing responses. We have previously reported that passive measurements of upper‐airway collapsibility in sedated subjects were similar to those in non‐REM sleep (Ayuse et al., 2004; Hoshino et al., 2009; Inazawa et al., 2005; Kobayashi et al., 2011). Active compensatory neuromuscular responses to partial upper‐airway obstruction have also been characterized in anesthetized subjects (Hoshino et al., 2009).…”
Section: Introductionmentioning
confidence: 61%
“…Airflow ( V ̄ ) was measured using a pneumotachometer (model 3,830, Hans Rudolph, Inc., Kansas City, MO, USA) and nasal pressure ( P N ) was measured using a differential pressure transducer (model 1100, Hans Rudolph, Inc.). The outflow from the valve attached to the nasal mask was then connected in series to the pneumotachometer and nasal mask, as described in a previous study (Kobayashi et al., 2011). Air leaks from the mouth were prevented by applying surgical tape across the lips.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anesthetizing and recovering patients without OSA in the head position elevated up to 6 cm from horizontal increases the stability of the airway. 122 It is useful to have patients with supine-related OSA in lateral or semiupright positions throughout the perioperative period. Although the role of fluid shift in worsening of OSA is not studied in the perioperative period, it may be prudent to restrict perioperative fluid administration in the elderly OSA patients and those with fluid retention states.…”
Section: Osa In Surgical Patientsmentioning
confidence: 99%